Development of performance evaluation instruments for faculty of national sports sciences lecturers - Masrun Masrun; Umar Umar; Khairuddin Khairuddin (Lambung Mangkurat University, 2024)
Assessing the performance of lecturers is a vital tool to ensure optimal education and learning aligned with established quality standards. However, there is currently no universally accepted tool for evaluating the performance of Faculty of Sport Science (FIK) lecturers in Indonesia. This research aims to create and standardize a performance evaluation instrument for FIK lecturers, focusing on Professional, Social, and Personal aspects. Employing a Research and Development (R&D) design with a procedural model, the standardization process involves several key steps. The study focuses on UNP FIK lecturers as test subjects. The standardization process encompasses compiling a framework, expert testing, a limited trial involving 30 samples, and a broader test with 82 samples. Practicality and effectiveness tests are also conducted. Data analysis, performed using the IBM SPSS program with a significance level of p < 0.05, supports the formation of a standardized instrument capable of nationally evaluating the performance of FIK lecturers.